Grave empire - Swan, Richard (Fiction writer) (Swan, Richard (Fiction writer) Great silence, 2025)
"From critically acclaimed author Richard Swan, Grave Empire begins the epic tale of an empire on the verge of industrial revolution, where sorcery and arcane practices are outlawed--and where an ancient prophecy threatens the coming end of days. Blood once turned the wheels of empire. Now it is money. A new age of exploration and innovation has dawned, and the Empire of the Wolf stands to take its place as the foremost power in the known world. Glory and riches await. But dark days are coming. A mysterious plague has broken out in the pagan kingdoms to the north, while in the south, the Empire's proxy war in the lands of the wolfmen is weeks away from total collapse. Worse still is the message brought to the Empress by two heretic monks, who claim to have lost contact with the spirits of the afterlife. The monks believe this is the start of an ancient prophecy heralding the end of days--the Great Silence. It falls to Renata Rainer, a low-ranking ambassador to an enigmatic and vicious race of mermen, to seek answers from those who still practice the arcane arts. But with the road south beset by war and the Empire on the brink of supernatural catastrophe, soon there may not be a world left to save..."--Amazon.ca.